General chemistry, second edition - Atkins, Peter William; Beran, J. A. ([S.l.] : Scientific Amer Inc, 1992)
This manual is an introduction and comprehensive reference book in the area of general chemistry. Features include: strategy sections, which help students to problem solve; end of chapter problems at varied difficulty levels in order to test the knowledge students have aquired; case studies with case problems; and numerous pedagogical aids. New to this edition is the addition of extra case problems and guest boxes, and the rewriting of chapters 1-4 with reorganized discussion of the role of electron pairs. Available with this text are a study guide, a solutions manual, an instructors manual, a test bank, overhead transparencies, videotaped lecture demonstrations and a videodisc of lecture demonstrations and chemical illustrations.
Keywords: general chemistry